Advances in Assessment, Reclamation and Management of Salt affected Soils for Sustainable Crop Production - Sanjay Arora (Journal of the Indian Society of Soil Science, 2026)
I feel highly honored and privileged to deliver the 21st Dr. R.S. Murthy Memorial Lecture in memory of a great soil scientist by virtue of his outstanding research contribution to pedology, soil survey, and land use planning, who acclaimed and celebrated both nationally and internationally. I pay my humble tribute to the late Dr. R.S. Murthy, in whose memory this lecture is dedicated, he was an eminent pedologist, a teacher par excellence, and will be forever remembered for his contributions in the field of Soil Survey. I owe a deep sense of gratitude to ISSS for bestowing this honour upon me. My thanks are also to the Ayodhya Chapter of the ISSS for organizing this lecture most immaculately. Choosing this topic is a great opportunity to focus on advances in delineation, reclamation and management of saline and sodic soils.